The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ptr.4753
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proinflammatory Biomarkers in THP1 Macrophages by Polyphenols Derived From Chamomile, Meadowsweet and Willow bark

Abstract: Antiinflammatory compounds in the diet can alleviate excessive inflammation, a factor in the pathogenesis of common diseases such as rheumatoid arthritis, atherosclerosis and diabetes. This study examined three European herbs, chamomile (Matricaria chamomilla), meadowsweet (Filipendula ulmaria L.) and willow bark (Salix alba L.), which have been traditionally used to treat inflammation and their potential for use as antiinflammatory agents. Aqueous herbal extracts and isolated polyphenolic compounds (apigenin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 31 publications
1
40
0
5
Order By: Relevance
“…Studies conducted in macrophages derived from THP-1 monocytes, demonstrated similar effects to these previously described [34,35,36]. Extracts of chamomile, meadowsweet, willow bark and isolated polyphenols present in these extracts as quercetin, apigenin and salicylic acid, were able to suppress the secretion of TNF-α and IL-6 without IL-1β modulation in THP-1 monocytes differentiated with phorbol -12-myristate-13-acetate (PMA) [38]. Inhibitory effects on TNF-α and Interleukin 8 (IL-8) were observed after treatment with an extract of Cydonia oblonga in THP-1 stimuled with LPS.…”
Section: Immune Function and Polyphenolsmentioning
confidence: 68%
“…Studies conducted in macrophages derived from THP-1 monocytes, demonstrated similar effects to these previously described [34,35,36]. Extracts of chamomile, meadowsweet, willow bark and isolated polyphenols present in these extracts as quercetin, apigenin and salicylic acid, were able to suppress the secretion of TNF-α and IL-6 without IL-1β modulation in THP-1 monocytes differentiated with phorbol -12-myristate-13-acetate (PMA) [38]. Inhibitory effects on TNF-α and Interleukin 8 (IL-8) were observed after treatment with an extract of Cydonia oblonga in THP-1 stimuled with LPS.…”
Section: Immune Function and Polyphenolsmentioning
confidence: 68%
“…CaCo-2 human colonic adenocarcinoma cells and THP1 human monocytic cells were cultured as previously described [8, 14]. At confluence, cells were starved for 12 h without FBS (replaced by 0.2% BSA) and treated for 1 h to 24 h with either 100 nM PMA or 200 nM IL-1 β .…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for the traditional use has been recently corroborated by multiple clinical trials (Langhorst et al ., ; Albrecht et al ., ). This is consistent, albeit in part, with the antioxidant and anti‐inflammatory properties of chamomile (McKay and Blumberg, ; Drummond et al ., ).…”
Section: Introductionmentioning
confidence: 97%